When the Going Gets Tough: Issue Environments and Gendered Negativity Strategies*. (9th October 2017) - Nelson, Kjersten
Abstract : Objective: In theory, gender expectations may influence candidate's negativity strategies. However, these gender expectations interact with other factors, such as party expectations and the election's issue environment. This study seeks to determine if candidate gender, opponent gender, and issue environment affect negativity strategies. Methods: The study analyzes the ads purchased by U.S. congressional candidates in the 2004 and 2008 election cycles. Results: The analyses show that gender and party expectations, moderated by the issue environment of the election, affect levels of negativity. Democratic women and Republican men appear to be particularly sensitive to these contextual changes. Conclusion: The results bolster other findings that gender expectations are moderated by party expectations, as well as context dependent. In addition, given that women report more reluctance to run for office based on the potential of being involved in a negative campaign, the results provide insight as to why more women are not running for office.